Pengaruh Pengungkapan Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), dan Shariah Compliance terhadap Kinerja Keuangan Perbankan Syariah - Azinuddin Syaiful Haq; Siti Murtiyani (At-Tauzi : Jurnal Ekonomi Islam, 2012)
The purpose of this study was to test empirically the influence of disclosure of Corporate Social Responsibility (CSR), Corporate Governance and Shariah Compliance in the financial performance of Islamic banking. Measurement of variables using the disclosure index Corporate Social Responsibility, Good Corporate Governance index and Shariah Compliance Index. While financial performance is measured using ROA (Return On Asset) in the syariah banking. Hypotheses were tested using multiple regression. The results of hypothesis testing showed that the coefficient β1 positive value 0.185 with p-value 0325, indicating that the CSR had no effect on the financial performance of Islamic banking. While the coefficient β2-value 2.030, p-value 0.030 showed that GCG effect on the financial performance of Islamic banking. In the coefficient β3-value 2.208 with p-value 0.003 indicates that the Shariah Compliance in effect on the financial performance of Islamic banking. CSR variable has no effect on the financial performance of Islamic banking shows that the role of Islamic banking in social activities in the community do not look real, so that Islamic banks need to increase social activity with increasing CSR funds directly to communities and revealed in its financial statements.